Metastatic Myoepithelial Carcinoma Ex Pleomorphic Adenoma of the Sublingual Salivary Gland - Ferreira, Ângela T (2023)
Myoepithelial carcinoma ex pleomorphic adenoma is a very rare malignant neoplasm of the salivary gland. Owing to its rarity, its clinical features and treatment are not well characterized. We describe a case of a patient who was referred to our department with a six-month history of a bulge on the right side of the floor of the mouth and a submandibular mass with progressive enlargement. The mass was resected, and an elective level I neck dissection was performed. Histological examination revealed myoepithelial carcinoma ex pleomorphic adenoma of the sublingual salivary gland. Thoracic computed tomography and biopsy revealed lung metastases. The patient died two years after the diagnosis